Effectiveness of virtual reality application technology for mathematical creativity - Flavia Aurelia Hidajat (Computers in Human Behavior Reports)
As a development of metaverse technology, virtual reality (VR) application technology will be utilized to create a visual experience of abstract mathematical concepts and boost students' mathematical creativity in mathematics education. Thus, this study explores whether abstract mathematical concepts at the college level with VR application technology effectively foster students' mathematical creativity. Ninety-six students followed learning-based VR in mathematics education in Jakarta, Indonesia. The effectiveness of the VR experience was measured through indicators of immersive, interactive, focused attention, and imaginative experiences from the use of VR application technology. Meanwhile, mathematical creativity was measured by the flexibility and originality of students' ideas. Students will implement VR applications designed with 3D objects. After the implementation of the VR application, the creativity questionnaire and the VR technology usage questionnaire became data collection methods. Data analysis used multiple linear regression analysis. The study's results showed a positive impact of virtual reality application technology's immersive and interactive experience on the flexibility of students' mathematical ideas in enhancing mathematical creativity. On the other hand, focused attention and imaginative experiences from virtual reality application technology influenced the acquisition of originality of mathematical ideas in enhancing students' mathematical creativity. This study is essential because it identifies the effectiveness of virtual reality experiences in visualizing abstract mathematical concepts and improving students' mathematical creativity.